Bobwhite Quail Population Dynamics: Relationships of Weather, Nesting, Production Patterns, Fall Population Characteristics, and Harvest in Missouri Quail - Jack A. Stanford (National Quail Symposium Proceedings, 2017)
For 25 years Missouri has investigated bobwhite quail (Colinus virginianus) behavior, production, and population response to 4 major types of weather. Ten population parameters are examined annually to compare effects of Normal, Wet-Deluge, Snow-Cold and Drought weather years on quail populations, Different types of weather are related to varying annual quail abundance by affecting productivity and survival and influencing relative levels of annual harvest and hunter interest. Normal and Wet-Deluge years yield favorable fall quail populations and satisfactory hunting. Years having winters of severe snow and cold have high breeder losses, low production, and reduced hunting success. In years having high temperature and drought in spring and summer, quail reproduction is inhibited, resulting in high losses of eggs and young,greatly reduced fall bird crops, and below-par hunting for many hunters. Recovery from weather-caused population lows usually occurs within 2 or 3 years after favorable weather conditions return. Reliable techniques for sampling have been developed to yield indices of annual production and hunting success. Production curves show the value of data on the distribution of peaks in hatching for understanding annual production and fall population levels of quail in Missouri. Such data form the basis for setting annual hunting regulations of bobwhite harvest.